2016
DOI: 10.24015/japm.2016.0023
|View full text |Cite
|
Sign up to set email alerts
|

Mineralocorticoid Receptor, A Promising Target for Improving Management of Low Back Pain by Epidural Steroid Injections

Abstract: Aim of review-Low back pain is a major health problem in United States and worldwide. In this review, we aim to show that mineralocorticoid receptor (MR) activation has a critical role in the initiation of immune and inflammatory responses, which in turn can impact the effectiveness of the currently used steroids for epidural injections in low back pain management since most steroids activate MR in addition to the primary target, glucocorticoid receptor (GR). Moreover, we would like to determine some of the be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Low back pain is a major health issue and common cause of chronic pain. It is prevalent in one third of the US population (Johannes et al, 2010 ; Ibrahim et al, 2016 ). It is the most common cause of chronic pain.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Low back pain is a major health issue and common cause of chronic pain. It is prevalent in one third of the US population (Johannes et al, 2010 ; Ibrahim et al, 2016 ). It is the most common cause of chronic pain.…”
Section: Introductionmentioning
confidence: 99%
“…Dexamethasone (DEX), a high potency, long acting glucocorticoid has been increasingly used as an epidural steroid injection for low back pain management, in part because it is viewed as a safer, non-particulate steroid (Schneider et al, 2015 ). Other steroids commonly used for epidural injections include betamethasone, 6-α-methylprednisolone and triamcinolone (Ibrahim et al, 2016 ). These clinically used steroids activate the glucocorticoid receptor (GR).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is not surprising that SPL has been investigated for its therapeutic potential in various neuropsychiatric disorders such as depression (Hinkelmann et al., 2016; Juruena et al., 2013; de Kloet et al., 2016), schizophrenia (Hasan et al., 2020; Wehr et al., 2017) or processing of stress responses (Schwabe, Höffken, et al., 2013; Schwabe, Tegenthoff, et al., 2013; Vogel et al., 2015, 2017). Furthermore and relevant for this study, MR has been shown to be involved in pain pathophysiology and MR antagonists including SPL reduce nociception and pain (Dong et al, 2012; Ibrahim et al., 2016; Li et al., 2018; Lilius et al., 2014; Tafelski et al., 2019).…”
Section: Introductionmentioning
confidence: 94%